2020
DOI: 10.1007/s13311-020-00882-x
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Motor Functional Recovery Following Immersive Virtual Reality–Based Limb Mirroring Therapy in Patients with Subacute Stroke

Abstract: Virtual reality (VR) is considered to be a promising therapeutic technology for the rehabilitation of upper extremities (UEs) poststroke. Recently, we designed and then implemented a neuroscientifically grounded VR protocol for the rehabilitation of patients with stroke. The system provides unilateral and bilateral limb mirroring exercises in a fully immersive virtual environment that may stimulate and activate the mirror neuron system in the brain to help patients for their rehabilitation. Twelve patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 47 publications
1
57
0
1
Order By: Relevance
“…24,25,[42][43][44] The recovery of impaired sensorimotor functions following intensive rehabilitative intervention may be associated with improved arm motor function. 23,59 Following this speculation, our newly developed VR system appears to be capable of promoting functional reorganization of the motor system that has been directly or indirectly affected by stroke.…”
Section: Discussionmentioning
confidence: 94%
“…24,25,[42][43][44] The recovery of impaired sensorimotor functions following intensive rehabilitative intervention may be associated with improved arm motor function. 23,59 Following this speculation, our newly developed VR system appears to be capable of promoting functional reorganization of the motor system that has been directly or indirectly affected by stroke.…”
Section: Discussionmentioning
confidence: 94%
“…In the case of VR interventions in stroke patients with affected ULs, leap motions are usually used in order to track the user's movements. Three of the included trials in our review used this method in their treatment protocol to regain the motor function of affected limbs in patients with subacute stroke ( 44 , 51 , 57 ). However, the remaining studies used the terms “virtual reality intervention” and “game-based intervention” interchangeably.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these limitations, we recommend conducting more robust, well-designed trials of larger sample sizes and longer follow-up periods to reach more definitive conclusions. Fourth, outcomes were assessed directly after the application of the VR interventions with a short follow-up period, ranging from 2 to 12 weeks ( 44 , 56 ). Therefore, we are not confident that the improvement in motor function following the implementation of VR protocols is long-lasting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a beneficial role of motor-related areas on the recovery of motor function following stroke [ 7 , 51 , 52 ]. Additionally, the connectivity related to these motor-related areas was improved and tended toward connectivity values of healthy participants after clinical intervention [ 11 , 53 , 54 ]. Regarding the bilateral SMA, previous studies have shown that these regions are mainly involved in motor planning and motor execution during voluntary movement [ 55 ].…”
Section: Discussionmentioning
confidence: 99%